Blockchain Technology: A Panacea for IoT Security Challenge - Adebayo, Nehemiah; Bajeh, Amos O.; Arowolo, Micheal; Udochuckwu, Erondu; Jesujana, Kayode; Ajayi, Mary; Abdulrasaq, Surajudeen; Onyemenam, John (EAI Endorsed Transactions on Internet of Things, 2022)
The Internet of Things (IoT) platforms, despite the wide range of application is not without loop holes of which cyberattackers can take advantage. In order to improve the platform’s security while also increasing other features, it has been proposed that blockchain technology be implemented in any IoT system. However, while blockchain technology has many advantages, it is important to consider other options because they all have their own drawbacks that may not be ideal for every use case situation. IoT network devices have limited computer power, storage space, and bandwidth. As a result, these systems are easily prone to assault than other network connected devices, such PCs, cell phones and tablets. With focus on IoT security challenges and the countermeasures offered by the blockchain technology, consensus algorithm, data encryption and smart contracts were discovered to be the common and effective algorithm employed by the blockchain technology in securing Iot systems over time.